Phylogeny, function and ecology in the deep evolutionary history of the mammalian forelimb. Issue 1949 (21st April 2021) - Lungmus, Jacqueline K.; Angielczyk, Kenneth D.
Abstract : Mammals are the only living members of the larger clade Synapsida, which has a fossil record spanning 320 Ma. Despite the fact that much of the ecological diversity of mammals has been considered in the light of limb morphology, the ecological comparability of mammals to their fossil forerunners has not been critically assessed. Because of the wide use of limb morphology in testing ecomorphological hypothesis about extinct tetrapods, we sought: (i) to estimate when in synapsid history, modern mammals become analogues for predicting fossil ecologies; (ii) to document examples of ecomorphological convergence; and (iii) to compare the functional solutions of distinct synapsid radiations. We quantitatively compared the forelimb shapes of the multiple fossil synapsid radiations to a broad sample of extant Mammalia representing a variety of divergent locomotor ecologies. Our results indicate that each synapsid radiation explored different areas of morphospace and arrived at functional solutions that reflected their distinctive ancestral morphologies. This work counters the narrative of non-mammalian synapsid forelimb evolution as a linear progression towards more mammalian morphologies. Instead, a disparate array of early-evolving shapes subsequently contracted towards more mammal-like forms.